2016
DOI: 10.1007/s00406-016-0708-3
|View full text |Cite
|
Sign up to set email alerts
|

Birth by cesarean section and schizophrenia: results from the multicenter FACE-SZ data-set

Abstract: Children born by cesarean section ("c-birth") are known to have different microbiota and a natural history of different disorders including allergy, asthma and overweight compared to vaginally born ("v-birth") children. C-birth is not known to increase the risk of schizophrenia (SZ), but to be associated with an earlier age at onset. To further explore possible links between c-birth and SZ, we compared clinical and biological characteristics of c-born SZ patients compared to v-born ones. Four hundred and fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
0
8
0
8
Order By: Relevance
“…Experimental studies described the changes in dopamine concentrations and changes in dopamine-mediated behaviors [ 24 ], as well as noradrenaline concentrations [ 25 ]. It is postulated that this difference in microbiota may affect the development of brain and the later increase in the risk of diseases such as schizophrenia [ 26 ]. The differences in the type of delivery and children’s cognitive development related to the effect of the gut microbiota may be explained by chemical signaling from the gut microbiota to the central nervous system, affecting memory, motivation, mood, and reactivity to stress [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies described the changes in dopamine concentrations and changes in dopamine-mediated behaviors [ 24 ], as well as noradrenaline concentrations [ 25 ]. It is postulated that this difference in microbiota may affect the development of brain and the later increase in the risk of diseases such as schizophrenia [ 26 ]. The differences in the type of delivery and children’s cognitive development related to the effect of the gut microbiota may be explained by chemical signaling from the gut microbiota to the central nervous system, affecting memory, motivation, mood, and reactivity to stress [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…not actually indicative of a schizophrenia-like phenotype. Finally, there is very little data on possible sources of dysbiosis, with Csection-a commonly suggested cause of dysbiosis (30)-found not to be associated with schizophrenia (31,32).…”
Section: Evidence For Dysbiosis In Schizophreniamentioning
confidence: 99%
“…Schizophrenia is a serious and disruptive mental disorder that has a substantial effect on public health (Collins et al, 2011). Schizophrenia and Cesarean birth are associated (Verdoux et al, 1997; Boksa and Ei-Khodor, 2003; Fond et al, 2016). For instance, Verdoux et al (1997) found that the incidence of early onset schizophrenia in a group of Cesarean births was 10 times higher than the incidence of late onset schizophrenia, which suggests that Cesarean birth is associated with the early onset of schizophrenia.…”
Section: Effect Of Cesarean Section On Children’s Psychological Healthmentioning
confidence: 99%